The genesis of Marxian thought (1843–1846): class, materialism, and Revolution (Temporalis, 2026)
The article analyzes the genesis of Marxian thought between 1843 and 1846 through three central axes: class perspective, the method of grasping reality, and the theory of social transformation. It is a theoretical essay guided by the critical-dialectical method that examines the fundamental works of the period. It discusses Feuerbach’s influence on the critique of Hegel’s conception of the State, then addresses the Franco-German Annals and the overcoming of the initial democratic position, identifying the proletariat as the historical subject of emancipation. Subsequently, it analyzes the Economic and Philosophical Manuscripts, highlighting the discovery of labor as the founding activity of social being and its relation to alienation. Finally, it discusses The German Ideology, where Marx develops an original theoretical synthesis that articulates different levels of abstraction. The path shows how, already in this period, Marx significantly advances in the articulated elaboration of the three fundamental pillars of his critique: class, materialism, and revolution.
Keywords: Class perspective; Historical materialism; Revolution theory; Young Marx